Identification and Determination of Berberine from Arcangelisia Flava, East Borneo - Riski Sulistiarini (Journal of Tropical Pharmacy and Chemistry, 2021)
Berberine is a compound that has various benefits but also has dangerous toxic effects. In Indonesia, the Regulation of the Head of the Food and Drug Supervisory Agency No. 10 of 2014 concerning the Prohibition of Producing and Circulating Traditional Medicines and Health Supplements Containing Coptis Sp, Berberis Sp, Mahonia Sp, Chelidonium Majus, Phellodendron Sp, Arcangelica Flava, Tinosporae Radix, and Catharanthus Roseus. Regulation No. 7 of 2018 (BPOM, 2018) also prohibits the presence of berberine in processed food. This research was conducted to determine the content of berberine compounds from the extract and stem fraction of Arcangelisia flava. The research was conducted by identifying the content of berberine by TLC method compared with Rf Berberine sulfate and determination of berberine content by HPLC method (High-Performance Liquid Chromatography) using column C-18 (ODS). Berberine content of methanol extract, n-hexane fraction, ethyl acetate fraction and Arcangelisia Flava methanol-water fraction were 0.0040, respectively; 0.0010; 0.0041, 0.0044%.